2022
DOI: 10.28934/jwee22.34.pp223-245
|View full text |Cite
|
Sign up to set email alerts
|

Instagram as a Means of Empowering Iranian Women by Focusing on Home-based Businesses

Fatemeh Mahdipour

Abstract: The focus of this study was to examine how Instagram can affect the empowerment of Iranian women by providing a platform for them to run their home-based businesses (HBBs). The data were collected through sixteen semi-structured interviews with Iranian women who ran their HBBs on Instagram, and Kabeer's empowerment framework was applied to the analysis. The results show that women's empowerment can be improved by running an HBB on Instagram. Participants in this study could achieve greater agency, facilitate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Running a business that gives women income will make them more confident and able to make decisions. (Mahdipour 2022). In contrast, this study identified many factors that shape the agency of female MSME Practitioners in Indonesia.…”
Section: Intersection and Female Msme Practitionersmentioning
confidence: 70%
“…Running a business that gives women income will make them more confident and able to make decisions. (Mahdipour 2022). In contrast, this study identified many factors that shape the agency of female MSME Practitioners in Indonesia.…”
Section: Intersection and Female Msme Practitionersmentioning
confidence: 70%